Predictors of clinical deterioration in patients with suspected COVID-19 managed in a 'virtual hospital' setting: a cohort study. Issue 3 (23rd March 2021) - Francis, Nick A; Stuart, Beth; Knight, Matthew; Vancheeswaran, Rama; Oliver, Charles; Willcox, Merlin; Barlow, Andrew; Moore, Michael
Abstract : Objective: Identify predictors of clinical deterioration in a virtual hospital (VH) setting for COVID-19. Design: Real-world prospective observational study. Setting: VH remote assessment service in West Hertfordshire NHS Trust, UK. Participants: Patients with suspected COVID-19 illness enrolled directly from the community (postaccident and emergency (A&E) or medical intake assessment) or postinpatient admission. Main outcome measure: Death or (re-)admission to inpatient hospital care during VH follow-up and for 2 weeks post-VH discharge. Results: 900 patients with a clinical diagnosis of COVID-19 (455 referred from A&E or medical intake and 445 postinpatient) were included in the analysis. 76 (8.4%) of these experienced clinical deterioration (15 deaths in admitted patients, 3 deaths in patients not admitted and 58 additional inpatient admissions). Predictors of clinical deterioration were increase in age (OR 1.04 (95% CI 1.02 to 1.06) per year of age), history of cancer (OR 2.87 (95% CI 1.41 to 5.82)), history of mental health problems (OR 1.76 (95% CI 1.02 to 3.04)), severely impaired renal function (OR for eGFR <30=9.09 (95% CI 2.01 to 41.09)) and having a positive SARS-CoV-2 PCR result (OR 2.0 (95% CI 1.11 to 3.60)). Conclusions: These predictors may help direct intensity of monitoring for patients with suspected or confirmed COVID-19 who are being remotely monitored by primary or secondary care services. Further research is needed to confirm our findings and identify the reasons for increased risk of clinical deterioration associated with cancer and mental health problems.